THE EMPOWERMENT OF WOMEN WITHIN THE PATRIARCHAL CULTURE OF THE KEEROM INDIGENOUS COMMUNITY - KORNELIA PEKEY (INJOSEDU: International Journal of Social and Education, 2026)
This study is oriented toward a critical analysis of the construction of patriarchal culture and its implications for gender inequality within the social life of Indigenous communities in Keerom Regency, Papua. Gender inequality is manifested through various forms of women’s subordination, including violence against women and children, customary marriage practices that restrict women’s educational continuity, and the limited participation of women in customary and social decision-making processes. Employing a critical paradigm and a qualitative case study approach, this study explores women’s lived experiences, forms of resistance to patriarchal domination, and empowerment strategies developed in response to gender-based power relations. Data are collected through observation, in-depth interviews, Focus Group Discussions (FGDs), and documentation. The data are subsequently analyzed using the Miles and Huberman model, which comprises data reduction, data display, and conclusion drawing and verification. Data credibility is strengthened through triangulation. Theoretically, this study integrates the perspectives of radical feminism, cultural feminism, and community empowerment to develop a contextually grounded model of Indigenous women’s empowerment. The proposed model is expected to strengthen women’s participation, educational access, legal protection, and institutional transformation toward a more inclusive and gender-equitable Indigenous social order.